Bangladesh – India Border Conflict: Challenges and Opportunities - Rahman, Md. Sayedur; Islam, Md. Shariful (Interdisciplinary Journal of Management and Social Sciences, 2024)
Geographically adjacent and friendly nations in South Asia are Bangladesh and India. The boundary’s approximate 5138 km total length is made up of a 4427 km land border and a 711 km water border. India and Bangladesh have a 4,096-kilometer border. While India has five border provinces, Bangladesh has 32 border districts. Bangladesh and India both have bilateral problems that date back to their inception. Since the early 1990s, the two countries’ economic ties have been expanding quickly. Due to border killing by the Indian Border Security Force, human trafficking, and other concerns between these two nations, the border issue has taken center stage. (BSF). The boundary between Bangladesh and India, according to the US-based news organization "Global Post," is the worst border line in the world. They are acting erratically near the boundary, killing, kidnapping Bangladeshis, violating human rights, and committing push-in offenses, among other things. The primary sources used in this study are scholarly books, scholarly journals, research papers, and other tertiary sources that are pertinent to the topic. Although the research is qualitative, a quantitative approach is also taken. This essay looks at the current problems surrounding border killing along the land border between India and Bangladesh, finding its causes and contributing factors as well as its detrimental effects on bilateral relations. The paper also includes a number of suggestions for preventing the issue of border killings along the land border between India and Bangladesh.